2022
DOI: 10.1097/mcg.0000000000001693
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Use and the Risk of Hepatocellular Carcinoma

Abstract: Introduction and Aim: The use of aspirin is a potential protective factor against the development of hepatocellular carcinoma (HCC). Therefore, we conducted a meta-analysis to evaluate the contribution of aspirin to the risk of HCC. Methods:We searched for PubMed and EMBASE through September 2021.Results: Eighteen studies (16 cohort, 2 case-control) were included. Aspirin users were less likely to develop HCC than nonusers [adjusted odds ratio (OR), 0.54; 95% confidence interval (CI): 0.44-0.66]. Stratified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The current study provides a detailed, updated analysis of the existing literature, with multiple additional subgroup analyses that provide confidence for the potential benefits of statins and inform clinical trial design. Some of the previous meta-analyses were limited by the use of odds ratios 13,14,16,52 for HCC risk, lack of PSM or IPTW analyses to balance baseline characteristics between study groups, 11,16,53 or did not thoroughly investigate sources of heterogeneity through detailed subgroup analyses. 11,54,55 A recent meta-analysis focusing on aspirin use and HCC risk pooled HRs after propensity score matching and determined similar findings (HR 0.54), although only 4 studies were included.…”
Section: In Context With Current Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The current study provides a detailed, updated analysis of the existing literature, with multiple additional subgroup analyses that provide confidence for the potential benefits of statins and inform clinical trial design. Some of the previous meta-analyses were limited by the use of odds ratios 13,14,16,52 for HCC risk, lack of PSM or IPTW analyses to balance baseline characteristics between study groups, 11,16,53 or did not thoroughly investigate sources of heterogeneity through detailed subgroup analyses. 11,54,55 A recent meta-analysis focusing on aspirin use and HCC risk pooled HRs after propensity score matching and determined similar findings (HR 0.54), although only 4 studies were included.…”
Section: In Context With Current Literaturementioning
confidence: 99%
“…Emerging data suggest that the use of statins, aspirin and metformin may be chemoprotective against HCC. [8][9][10][11][12] However, prior meta-analyses on this topic had some limitations such as pooling odds ratios that are not time-to-event measurements, 11,[13][14][15][16] or pooling data that had not been adequately adjusted for background differences in treated versus untreated patients. There have also been several recent relevant large studies that were not included in previous meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis focusing on dose-effect relationship between aspirin and cancer risk revealed that high frequency or high dose use of aspirin might increase lung and prostate cancer risks, while low-dose of aspirin use could prevent colorectal cancer ( Wang L. et al, 2021 ). Contrarily, a meta-analysis in hepatocellular carcinoma (HCC) (2 case-control and 16 cohort studies included) showed that the use of aspirin was associated with a lower risk of liver cancer, but not in a dose-dependent or a duration-dependent relationship ( Wang et al, 2022 ). Interestingly, the meta-analysis in HCC concluded that aspirin had protective effects against HCC in patients with hepatitis B virus or hepatitis C virus infection ( Wang et al, 2022 ), which was also supported by a nationwide study of patients with chronic viral hepatitis in Sweden ( Simon et al, 2020 ).…”
Section: Clinical Outcomes Of Non-steroidal Anti-inflammatory Drugs I...mentioning
confidence: 99%
“…Contrarily, a meta-analysis in hepatocellular carcinoma (HCC) (2 case-control and 16 cohort studies included) showed that the use of aspirin was associated with a lower risk of liver cancer, but not in a dose-dependent or a duration-dependent relationship ( Wang et al, 2022 ). Interestingly, the meta-analysis in HCC concluded that aspirin had protective effects against HCC in patients with hepatitis B virus or hepatitis C virus infection ( Wang et al, 2022 ), which was also supported by a nationwide study of patients with chronic viral hepatitis in Sweden ( Simon et al, 2020 ). Moreover, according to a systematic review and meta-analysis of all observational studies on aspirin use and digestive-tract cancers up to March 2019, aspirin use was related to lower risks in various digestive malignancies, including colorectal cancer (45 studies), squamous-cell esophageal cancer (13 studies), adenocarcinoma of the esophagus and gastric cardia (10 studies), stomach cancer (14 studies), hepatobiliary cancer (5 studies) and pancreatic cancer (15 studies) ( Bosetti et al, 2020 ).…”
Section: Clinical Outcomes Of Non-steroidal Anti-inflammatory Drugs I...mentioning
confidence: 99%
“…Magnitude of HCC risk reduction may be different between Asian (OR, 0.59) and Western (OR, 0.67) populations, HBV (OR, 0.70) and HCV (OR, 0.41) infection, and chronic liver disease (OR, 0.46) and general (OR, 0.65) population, whereas longer duration of aspirin intake did not enhance HCC risk reduction (OR, 0.62 vs. 0.63). 59,60 In an analysis of national health insurance database in Korea, including 329,635 adults with chronic hepatitis B, 10-year HCC incidence was 9.5% in the aspirin-treated group and 11.3% in the untreated group (adjusted subdistribution hazard ratio [aSHR], 0.85; 95% CI, 0.78-0.92). 61 No HCC risk reduction was observed in cirrhosis patients (aSHR, 1.00; 95% CI, 0.85-1.18).…”
Section: Accepted Manuscriptmentioning
confidence: 99%